Abtastregelung linearer verteilt-parametrischer Systeme unter Verwendung allgemeiner Halteglieder - Harkort, Christian; Deutscher, Joachim (Methoden und Anwendungen der Regelungstechnik, 2011)

An approach for the construction of the control input operator associated to boundary control systems - Harkort, Christian; Deutscher, Joachim (Workshop on Multidimensional Systems 2013, 2013)

A parametric approach to finite-dimensional control of linear distributed-parameter systems - Deutscher, Joachim; Harkort, Christian (International Journal of Control, 2010)

Approximation verteilt-parametrischer Systeme zweiter Ordnung mittels Krylov-Unterraummethoden - Deutscher, Joachim; Harkort, Christian (at - Automatisierungstechnik, 2013)

Discrete-time modal state reconstruction for infinite-dimensional systems using generalized sampling - Harkort, Christian; Deutscher, Joachim (IFAC-PapersOnLine, 2011)
Keywords: Generalized sampling; Non-asymptotic state reconstruction; Infinite-dimensional system; State feedback control; Sampled-data control

Entwurf endlich-dimensionaler Regler für lineare verteilt-parametrische Systeme durch Ausgangsbeobachtung - Deutscher, Joachim; Harkort, Christian (at - Automatisierungstechnik, 2010)

Finite-dimensional observer-based control of linear distributed parameter systems using cascaded output observers - Harkort, Christian; Deutscher, Joachim (International Journal of Control, 2011)
The synthesis of compensators for linear distributed-parameter systems on the basis of a finite-dimensional approximation is a classical technique. This so-called early-lumping approach suffers from the occurrence of spillover which means that the closed-loop dynamics is deteriorated by the neglected dynamics. In this contribution, an early-lumping compensator design is presented that overcomes the spillover problem by using certain fictitious outputs which can be reconstructed without spillover and that suppress the contributions of the unmodelled dynamics. When the new outputs are used for the compensator instead of the available measurements, the perturbation of the closed-loop spectrum, caused by spillover, can be reduced to an arbitrary extent. It is shown that the worst-case eigenvalue perturbation decreases exponentially with respect to the compensator order so that the spillover can be reduced systematically. In addition, an a priori estimate for the compensator order, that guarantees a prescribed maximal eigenvalue perturbation, is presented. The proposed design procedure is demonstrated for the control of an Euler-Bernoulli beam with Kelvin-Voigt damping. © 2011 Taylor & Franci
Keywords: early-lumping approach; eigenvalue enclosure; finite-dimensional control; Riesz-spectral system; spectrum analysis; spillover reduction

Führungs- und Störgrößenaufschaltungen für lineare verteilt-parametrische Systeme - Deutscher, Joachim; Harkort, Christian (at - Automatisierungstechnik, 2010)
In this article the design of reference and disturbance feedforward controllers is considered for linear distributed-parameter systems, which are Riesz-spectral systems. Explicit expressions are derived for the feedforward controller. The design uses a two-degree-offreedom structure which enables an independent computation of the feedforward controller and of a state feedback controller that assigns the closed loop dynamics. A heat conductor is used to demonstrate the results of the contribution in simulations. © Oldenbourg Wissenschaftsverla
Keywords: Disturbance feedforward control; Linear distributed-parameter systems; Parametric approach; Reference feedforward control; Two-degrees-of-freedom control

I4Copter: An Adaptable and Modular Quadrotor Platform - Ulbrich, Peter; Kapitza, Rüdiger; Harkort, Christian; Schmid, Reiner; Schröder-Preikschat, Wolfgang (Proceedings of the 26th ACM Symposium on Applied Computing, 2011)
Quadrotor helicopters are micro air vehicles with vertical take-off and landing capabilities controlled by varying the rotation speed of four fixed pitch propellers. Due to their rather simple mechanical design they have grown to popularity as platform for various research projects. Despite most of them being individually highly successful, they are typically tailored to a specific purpose making it hard to utilise them for further research and education. In this paper, we present the novel design of the I4Copter quadrotor. It has been developed to provide a stable demonstration quadrotor platform for various kinds of research and education projects targeting cross-field challenges in real-time and embedded systems, distributed systems, robotics and cybernetics. The modular and open architecture of our platform allows an application- specific, fine-grained extension, adaption and replacement of software and hardware components. The safe extensibility is supported by strict temporal and spatial isolation between the software modules. We validated our approach by two distinct cross-field use cases: an evaluation platform for modularised control algorithms enabling trajectory tracking and an implementation that is resilient to transient hardware errors. © 2011 ACM.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.i4copt
Keywords: I4Copter; Safety-critical mission scenario; Real-time application development; Static analysis; Research demonstrator; Quadrocopter; Quadrotor; Quadcopter

Krylov subspace methods for linear infinite-dimensional systems - Harkort, Christian; Deutscher, Joachim (IEEE Transactions on Automatic Control, 2011)

Parametric approach to the decoupling of linear distributed-parameter systems - Deutscher, Joachim; Harkort, Christian (IET Control Theory and Applications, 2010)
In this study the input-output decoupling of linear distributed-parameter systems with distributed control and distributed measurement is considered. The decoupling problem is formulated as an eigenstructure assignment problem for distributed-parameter systems, which is solved using the parametric approach. The resulting static state feedback controller exponentially stabilises the closed-loop system and decouples the reference transfer behaviour with respect to the first p dominant closed-loop modal states. The residual dynamics are taken into account by compensating further dominant eigenvalues with transmission zeros, so that they do not influence the reference transfer behaviour. A heat conductor is used to demonstrate the design procedure which is also compared with an early lumping approach. © 2010 The Institution of Engineering and Technolog

Parametric approximation of connected Euler-Bernoulli beams with variable beam lengths - Harkort, Christian; Deutscher, Joachim (MATHMOD 2012, 2012)

Parametric state feedback design for second-order Riesz-spectral systems - Deutscher, Joachim; Harkort, Christian (10th European Control Conference 2009, 2009)

Parametric state feedback design of linear distributed-parameter systems - Deutscher, Joachim; Harkort, Christian (International Journal of Control, 2009)
Keywords: Decoupling control; Eigenvalue assignment; Linear multi-input distributed-parameter systems; Parametric approach; Riesz-spectral operators

Reduktion von Spillover für lineare verteilt-parametrische Systeme - Harkort, Christian; Deutscher, Joachim (Methoden und Anwendungen der Regelungstechnik, 2009)

Spillover reduction for linear distributed-parameter systems using dynamic extensions - Harkort, Christian; Deutscher, Joachim (10th European Control Conference 2009, 2009)

Stability and passivity preserving Petrov-Galerkin approximation of linear infinite-dimensional systems - Harkort, Christian; Deutscher, Joachim (Automatica, 2012)
This contribution presents two approximation methods for linear infinite-dimensional systems that ensure the preservation of stability and passivity. The first approach allows one to approximate internal source free infinite-dimensional systems such that the resulting approximation is a port-controlled Hamiltonian system with dissipation. The second method deals with the class of systems that are not required to have conjugated outputs but only a dissipative system operator. It yields approximations with a dissipative system matrix for which bounds of their stability margin are provided. Both approaches are based on a state space formulation of the infinite-dimensional system. This makes it possible to use the Petrov-Galerkin approximation whose free parameters are partly used for achieving the structure preservation. Since still free parameters remain, further application specific objectives, such as, e.g., moment matching, can be achieved. Both approaches are applied to the approximation of an Euler-Bernoulli beam. © 2012 Elsevier Ltd. All rights reserve
Keywords: Linear infinite-dimensional systems; Port Hamiltonian systems; Structure preservation; System approximation

Structure-preserving approximation of distributed-parameter second-order systems using Krylov subspaces - Deutscher, Joachim; Harkort, Christian (Mathematical and Computer Modelling of Dynamical Systems, 2014)
Keywords: Galerkin approach; Krylov subspace methods; linear distributed-parameter systems; moment matching; second-order systems; structure preservation

Strukturerhaltende Approximation linearer verteilt-parametrischer PCHD-Systeme - Harkort, Christian; Deutscher, Joachim (at - Automatisierungstechnik, 2012)
In this contribution an approximation approach for linear distributed-parameter port controlled Hamiltonian systems with damping (PCHD systems) is presented that allows for the preservation of the PCHD structure of the original system. Futhermore, it is possible to assure that the stability margin of the approximation satisfies a lower bound that depends on the dissipativity of the infinitedimensional system operator. The presented approximation method is based on a generalized version of the Petrov-Galerkin approximation and has free parameters that can be used to achieve approximations with matching moments. The results of the paper are demonstrated by approximating a heat conducting system. © Oldenbourg Wissenschaftsverla
Keywords: Krylov subspace method; Linear infinite-dimensional systems; PCHD systems; Structure preserving approximation

Taking Control: Modular and Adaptive Robotics Process Control Systems - Ulbrich, Peter; Franzmann, Florian Peter; Harkort, Christian; Hoffmann, Martin; Klaus, Tobias; Rebhan, Anja; Schröder-Preikschat, Wolfgang (Proceedings of the 10th IEEE International Symposium on Robotic and Sensors Environments, 2012)
Robotics systems usually comprise sophisticated sensor and actuator systems with no less complex control applications. These systems are subject to frequent modifications and extensions and have to adapt to their environment. While automation systems are tailored to particular production processes, autonomous vehicles must adaptively switch their sensors and controllers depending on environmental conditions. However, when designing and implementing the process control system, traditional control theory focuses on the control problem at hand without having this variability in mind. Thus, the resulting models and implementation artefacts are monolithic, additionally complicating the real-time system design. In this paper, we present a modularisation approach for the design of robotics process control systems, which not only aims for variability at design-time but also for adaptivity at run-time. Our approach is based on a layered control architecture, which includes an explicit interface between the two domains involved: control engineering and computer science. Our architecture provides separation of concerns in terms of independent building blocks and data flows. For example, the replacement of a sensor no longer involves the tedious modification of downstream filters and controllers. Likewise, the error-prone mapping of high-level application behaviour to the process control system can be omitted. We validated our approach by the example of an autonomous vehicle use case. Our experimental results demonstrate ease of use and the capability to maintain quality of control on par with the original monolithic design. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.taking
Keywords: Architecture; Software Design; Operating Systems; Robotics and Automation; Sensor Systems; Control Engineering; Measurement System Data Handling; AORTA; ARES

Vollständige Modale Synthese eines Wärmeleiters - Deutscher, Joachim; Harkort, Christian (at - Automatisierungstechnik, 2008)